(untitled) (Research, Society and Development, 2020)
Flaxseed (Linum usitatissimum L.) has polyunsaturated fatty acids, fibers, phenolic compounds, antioxidants and other bioactive substances, which gives it status as a functional food. This study aimed to verify the physical-chemical composition, the amount of phenolic compounds in flaxseed flour, and the fatty acid composition of the oil from that flour. Flaxseed flour was characterized by moisture, ash, protein, lipids, carbohydrates, caloric value and phenolic compounds. The oil was extracted from this flour, which was analyzed in a chromatograph to determine its fatty acids. Flaxseed flour showed 4.85% moisture, 3.28% ash, 17.56 protein, 41.31% lipids, 33.0% carbohydrates, 574.03 calories and 211.53 mg EAG / 100g of phenolic compounds. The chromatogram of linseed oil showed a predominance of unsaturated fatty acids (95.1%), with the highest concentration being linolenic acid (C18: 3 - 53.58%), followed by oleic acid (C18: 1 - 25.98%) ), linoleic (C18: 2 - 15.54%) and to a lesser extent, saturated stearic (C18: 0 - 4.24%) and palmitic (C16: 0 - 0.66%). The induction period (PI) of flaxseed oil reduced with increasing temperature, showing that higher temperatures (110 ° C and 120 ° C) promoted less oxidative stability of this oil. Due to the results obtained, it is suggested to observe how to conserve flaxseed flour and oil and the products that contain them in their composition. And evaluate the content of polyunsaturated fatty acids (PUFA) in products added with flour and flaxseed oil, especially those submitted to temperatures above 120 ° C, as in bakery products.